ANALISIS PRAKTEK PERKEBUNAN TERBAIK PEKEBUN SWADAYA DESA BENTENG HULU KECAMATAN MEMPURA KABUPATEN SIAK - Aulia Triana; Sakti Hutabarat; Syaiful Hadi (DINAMIKA PERTANIAN, 2022)
This research was conducted at the Sawit Jaya Cooperative in Benteng Hulu Village, Mempura District, Siak Regency. The purpose of this research is to find out what the social characteristics of oil palm smallholders are, what the economics of implementing governance by oil palm smallholders are, and how it applies between smallholder governance versus RSPO standard governance. The research population is independent oil palm smallholders who use quantitative and qualitative analysis. Measurement of the implementation of smallholder oil palm plantation governance is carried out using a scale starting from the achievement of indicators, criteria, and principles in RSPO certification. The population in this study were the oil palm farmers of the Sawit Jaya Cooperative in Benteng Hulu Village, Mempura District, Siak Regency. The achievement of implementing RSPO principles in the governance of oil palm plantations owned by independent smallholders is very far from the RSPO standard. The results showed that the implementation of the RSPO standard was still low. The farmers and their cooperatives should be upgraded and their skills on the RSPO standard.